Developing a researcher identity: A reflective narration of postgraduate students’ supervision experiences in a research project - Madikizela-Madiya, Nomanesi; Goba, Barbara Busisiwe; Nkambule, Thabisile (South African Journal of Higher Education, 2016)
Postgraduate students go through diverse experiences as they struggle with the construction of their identities towards becoming ‘researchers’. Such diversity is even more pronounced when they are supervised within a large-scale research project where they interact with a number of supervisors from different disciplines. This article analyses postgraduate students’ learning experiences on becoming researchers in a research project using situated learning theory. The analysis focuses on different experiences such as mentoring towards conference presentations and writing for publication. We suggest that in addition to the completion of doctoral or master’s degrees, postgraduate supervision through large projects may facilitate the development of researcher identity and enhance institutions’ research outputs as long as there is trust, collaboration and devolution of power among the members of a research community of practice.